Blood pressure reduction following treatment with positive airway pressure in sleep apnea: data from the European Sleep Apnea Database. (25th November 2020) - Svedmyr, S; Grote, L; Zou, D; Bailly, S; Lombardi, C; Ludka, O; Bonsignore, M; Schiza, S; Kvamme, J.A; Basoglu, O.K; Verbraecken, J; Hedner, J
Abstract: Introduction: Positive airway pressure (PAP) treatment modifies blood pressure (BP) in patients with obstructive sleep apnea (OSA). We aimed to explore which factors that influence the BP response to PAP therapy in the European Sleep Apnea Database (ESADA). Methods: A total of 2662 OSA patients with PAP therapy ≥90 days were included in the analysis (74% male, age 55±11 years, body mass index 32.3±6.1 kg/m 2, 47% hypertensives, apnea-hypopnea index 40±24 events/h, treatment duration 1.0±1.1 years, PAP compliance 5.2±1.9 h/day). Anthropometric data, co-medications and office BP were assessed at baseline and follow-up visit. Results: Systolic and diastolic BP were modestly reduced after PAP therapy compared to baseline (133±17 vs. 134±17 mmHg, 78±11 vs. 81±11 mmHg, p<0.001, respectively). In a generalized linear model controlling for anthropometric, PAP compliance and follow-up time, severe OSA at baseline (β [95% CI] −3.2 [−5.1 to −1.3], p=0.001), hypertension status (−2.0 [−3.3 to −0.7], p=0.003), weight reduction >2 kg at follow up (−2.0 [−3.7 to −0.4], p=0.016), and use of auto-adjusted PAP (−1.3 [−2.5 to −0.02], p=0.046) were associated with a reduction of systolic BP at follow-up. Conclusions: BP reduction following PAP treatment in patients with moderate to severe OSA was modest. We identified several predictors of a favorable BP response including the use of auto adjusted PAP. Our findings suggest that weight reduction strategies in addition to PAP treatment should be considered to obtain adequate BP control in OSA patients. Funding Acknowledgement: Type of funding source: Other. Main funding source(s): European Respiratory Society funded Clinical Research Collaboration (2015-2020)